2009
DOI: 10.5539/ibr.v2n2p99
|View full text |Cite
|
Sign up to set email alerts
|

Audit Firm Tenure and Auditor Reporting Quality: Evidence in Malaysia

Abstract: The main purpose of the study is to examine the relationship between audit firm tenure and auditor reporting quality in Malaysia. This study employs well-established going concern model of logistic regression. Our findings show that audit firm tenure is positively significant relationship with auditor reporting quality. Future research should consider other importance variables that may affect the auditor reporting quality such as non-audit services, and audit partner tenure. However, in sum, this study is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Demikian yang dikemukakan oleh Veronica Sylvia, dkk (2011) menyatakakan bahwa jangka waktu audit yang terlalu lama menurunkan kualitas audit, tetapi terdapat temuan juga bahwa jika dilakukan rotasi audit akan menurunkan kualitas audit. Hal senada dikemukakan oleh Shafie et al (2009) menyatakan jika klien tidak pernah mengganti auditor sejak terdaftar di Bursa Malaysia, ada kecenderungan untuk mengeluarkan pendapat bersih meskipun klien menderita masalah keuangan yang jelas.…”
Section: Kajian Teoriunclassified
“…Demikian yang dikemukakan oleh Veronica Sylvia, dkk (2011) menyatakakan bahwa jangka waktu audit yang terlalu lama menurunkan kualitas audit, tetapi terdapat temuan juga bahwa jika dilakukan rotasi audit akan menurunkan kualitas audit. Hal senada dikemukakan oleh Shafie et al (2009) menyatakan jika klien tidak pernah mengganti auditor sejak terdaftar di Bursa Malaysia, ada kecenderungan untuk mengeluarkan pendapat bersih meskipun klien menderita masalah keuangan yang jelas.…”
Section: Kajian Teoriunclassified
“…Some research that has uncovered the relationship between tenure and audit quality includes works by Geiger and Raghunandan (2002), Johnson (2002), Myers et al (2003), Manry, et al (2003), Carcello and Nagy (2004), Ghosh and Moon (2005), Carey and Simnett (2006), Knechel and Vanstraelen (2007), Shafie et al (2009), AlThuneibat et al (2010. Most of the research in America rejects the statement that the duration of the relationship between an auditor and client brings negative effects to an audit's quality (for example like Geiger and Raghunandan 2002;Myers et al 2003;Carcello and Nagy 2004;and Ghosh and Moon 2005).…”
Section: Auditor Tenure and Audit Qualitymentioning
confidence: 99%
“…Carcello and Nagy (2004) find the evidence that cheating in financial reporting is more likely to happen in the first three years of an auditor's tenure. Shafie et al (2009), who did their research in Malaysia, shows that auditors' tenure has significant positive effects on the quality of the auditors' reports.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence provided by those studies is mixed. While studies that used data from Belgian and Australian firms reported that long-term auditor client relationships significantly reduce the auditors' willingness to qualify audit reports (Vanstraelen, 2000;Carey and Simnett, 2006), studies from U.S., Belgian, Spain, Australia, and Malaysia found evidence that the propensity to issue a going concern audit opinion (namely for distressed firms) does not depend on the auditors' tenure (Geiger and Raghunandan, 2002;Vanstraelen, 2002;Barbadillo et al, 2004;Knechel and Vanstraelen, 2007;Jackson et al, 2008;Shafie et al, 2009), and that the abolishment of mandatory audit rotation even increased the likelihood of auditors issuing goingconcern audit opinions to distressed firms (Barbadillo et al, 2009). The level of analysis (audit firm-level versus engagement partner level) and the control variables included in the research models may explain the inconsistency between the results.…”
Section: Francis Andmentioning
confidence: 99%
“…Carey and Simnett (2006) conducted their analysis at the audit-partner level, but all the other studies used the audit-firm level. Regarding the control variables, generally, all studies included a set of client firm characteristics related with age, size, leverage and several controls for financial performance, but only a few studies included corporate governance controls (Geiger and Raghunandan, 2002;Shafie et al, 2009) and industry controls (Carey and Simnett, 2006;Jackson et al, 2008;Barbadillo et al, 2009). All studies controlled for audit firm size and audit pricing, but only three studies controlled for auditor industry specialization (Barbadillo et al, 2004;Jackson et al, 2008;Barbadillo et al, 2009).…”
Section: Francis Andmentioning
confidence: 99%